2021
DOI: 10.1371/journal.pone.0254410
|View full text |Cite
|
Sign up to set email alerts
|

Pressure measurement in the reticulum to detect different behaviors of healthy cows

Abstract: The aim of the current study was to investigate the relation between reticulorumen contractions and monitored cow behaviors. A purpose-built pressure measuring device was used and shown to be capable of detecting the known contraction patterns in the reticulorumen of four rumen-fistulated cows. Reticular pressure data was used to build a random forest algorithm, a learning algorithm based on a combination of decision trees, to detect rumination and other cow behaviors. In addition, we developed a peak-detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…With regard to the minor peak shown in our study, the CD was ~8 s, and ICI was ~40–45 s, which are consistent with those obtained by Braun and colleagues for the eating and resting behaviour patterns. In a recent study, where the RRCR was measured with water filled open-tipped catheter (Scheurwater et al ., 2021), the ICI for rumination was around 48 s, and for eating was 34 s; however, the large variation between the behaviours did not allow classification of the patterns by using a set threshold (Scheurwater et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the minor peak shown in our study, the CD was ~8 s, and ICI was ~40–45 s, which are consistent with those obtained by Braun and colleagues for the eating and resting behaviour patterns. In a recent study, where the RRCR was measured with water filled open-tipped catheter (Scheurwater et al ., 2021), the ICI for rumination was around 48 s, and for eating was 34 s; however, the large variation between the behaviours did not allow classification of the patterns by using a set threshold (Scheurwater et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Methods for measuring the RRCR are classified as either invasive or non-invasive, depending on whether surgery is required to apply the measuring device (Braun and Rauch, 2008; Han et al ., 2022). Invasive methods include electrodes applied in the forestomach to measure electrical activity (Plaza et al ., 1996; Wierzbicka et al ., 2021) and placement within the reticulum of air- or water-filled pressure devices (Holtenius et al ., 1971; Egert-McLean et al ., 2019; Scheurwater et al ., 2021). Non-invasive methods include ultrasonography and indwelling reticuloruminal boluses, which directly measure reticular movement; less direct non-invasive methods include clinical examination, auscultation and palpation of the paralumbar fossae; however, they cannot differentiate between primary and secondary cycles (Grünberg and Constable, 2009).…”
mentioning
confidence: 99%
“…A sample frequency of 2 Hz is sufficiently accurate for the identification of rumination (Scheurwater et al, 2021). Furthermore, potential associations between the reticulorumen contraction cycles and different types of cow behaviour have been investigated previously Scheurwater et al, 2021). We previously found that the time between two contraction cycles is possibly shortest during eating, but the large variation precluded us from setting a clear threshold to separate eating from other behaviour (Scheurwater et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Reticular contractions could be detected as well by measuring the actual pressure in the reticulum. In a proof of principle study, we previously showed that reticular pressure can be measured with a device based on water-filled open-tipped catheters in cannulated cows (Scheurwater et al, 2021) and found that to be able to detect the distinct three-peak pattern of pressure differences during rumination, the sampling frequency needs to be appropriate. A sample frequency of 2 Hz is sufficiently accurate for the identification of rumination (Scheurwater et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation